2011
DOI: 10.1088/0004-637x/733/1/70
|View full text |Cite
|
Sign up to set email alerts
|

XMM-NEWTONX-RAY AND ULTRAVIOLET OBSERVATIONS OF THE FAST NOVA V2491 Cyg DURING THE SUPERSOFT SOURCE PHASE

Abstract: Two XMM-Newton observations of the fast classical nova V2491 Cyg were carried out in short succession on days 39.93 and 49.62 after discovery, during the supersoft source (SSS) phase, yielding simultaneous X-ray and UV light curves and high-resolution X-ray spectra. The first X-ray light curve is highly variable, showing oscillations with a period of 37.2 minutes after an extended factor of three decline lasting ∼ 3 hours, while the second X-ray light curve is less variable. The cause of the dip is currently u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(112 citation statements)
references
References 60 publications
(92 reference statements)
0
111
0
Order By: Relevance
“…Although these distances have been inferred with the maximum-magnitude rate-of-decay (MMRD) relationship and these values may thus be highly uncertain (the relationship does not hold for RNe and sometimes is not very precise for CNe, moreover the nova had a rare secondary optical maximum), the optical and especially the supersoft X-ray luminosity in the outburst indicate that the distance cannot be much smaller. Especially the large supersoft X-ray flux (Page et al 2010;Ness et al 2011) is evidence of a distance of at least 10 kpc, otherwise the WD would have been underluminous compared with the models of the same high effective temperature (from 9 × 10 5 to a 10 6 K, see Starrfield et al 2012;Wolf et al 2013) and also with previous observations of novae in the SSS phase (see Orio 2012, for a review). We analysed the same dataset with the PDM method and found that the 0.02885 days period is most probably a daily alias of a 0.02655 days (38.23 min) period, which is very close to the one we found in X-rays.…”
Section: Timing Analysismentioning
confidence: 56%
“…Although these distances have been inferred with the maximum-magnitude rate-of-decay (MMRD) relationship and these values may thus be highly uncertain (the relationship does not hold for RNe and sometimes is not very precise for CNe, moreover the nova had a rare secondary optical maximum), the optical and especially the supersoft X-ray luminosity in the outburst indicate that the distance cannot be much smaller. Especially the large supersoft X-ray flux (Page et al 2010;Ness et al 2011) is evidence of a distance of at least 10 kpc, otherwise the WD would have been underluminous compared with the models of the same high effective temperature (from 9 × 10 5 to a 10 6 K, see Starrfield et al 2012;Wolf et al 2013) and also with previous observations of novae in the SSS phase (see Orio 2012, for a review). We analysed the same dataset with the PDM method and found that the 0.02885 days period is most probably a daily alias of a 0.02655 days (38.23 min) period, which is very close to the one we found in X-rays.…”
Section: Timing Analysismentioning
confidence: 56%
“…In general, the atmosphere models have a steeper Wien tail of the spectrum than the blackbody, because of the presence of deep absorption lines and absorption edges seen in the high-resolution X-ray spectra (e.g. Ness et al , 2011). Thus to match the specific profile of the supersoft fluxes, a model atmosphere is required to obtain more reliable parameters than with a simple blackbody.…”
Section: Comparison Of Blacbody and Atmospheric Model Sedmentioning
confidence: 99%
“…(2010) have only assumed solar abundances for simplicity while working with the NLTE expanding atmosphere models and Ness et al (2011) have found consistent fits using static NLTE atmosphere models with fixed abundances where oxygen abundance was in a range O/O =10-30. This latter model has similar abundances to what we derived in this study.…”
Section: Discussionmentioning
confidence: 91%
“…The spectra have very broad lines with complex profiles and large expansion velocities (∼4000-6000 km s −1 ) (Lynch et al 2008;Tomov et al 2008). V2491 Cyg shows both the hard X-ray and the soft X-ray components during the outburst stage (analysis can be found in Page et al 2010;Ness et al 2011). Ibarra et al (2009) show that V2491 was a persistent X-ray source using archival ROS AT , XMMNewton, and Swift data during its quiescent phase before the optical outburst.…”
Section: Introductionmentioning
confidence: 99%